Organizing vocational education and training in schools: A case study of Australian Governments’ educational policies - CUI, Guihua (Advances in Social Sciences Research Journal, 2020)
Australian Governments of different levels have initiated and carried out some policies to reform vocational education and training in schools to ensure school to work successful transition. This article takes the New Framework as the target policy for analysis, supplemented by other related policies to investigate Governments’ purposes, principles and measures for organizing vocational education and training in schools. Dramaturgical coding method, together with excerpt-commentary analysis, has been adopted in the policy analysis. It is found that the partnerships among different levels and different agencies are key to the organizational changes in the success of vocational education and training in schools in effecting a seamless work/study transition. This approach offers an informed representation of the information that is conveyed in the New Framework by vividly interpreting its terms and conventions. The most important factor promoted by these policies was the promotion of partnerships between schools and industries.